OPTIMIZATION OF MAINTENANCE OF GENSETS USING EXPERT SYSTEMS FOR FAULT DIAGNOSIS - Željko Hederić; Venco Ćorluka; Dejan Barešić (Journal of Energy Technology, 2024)
The usage of expert systems simplifies the determination of the technological condition of the genset, i.e. the fault diagnosis. This results in the optimization of maintenance in technical workshops, whichparticularly comes into play in military systems in which a great number of technical resources must be maintained. The expert system is based on the “Knowledge Base”, obtained by researching andcollecting data from professionals who have years of experience in the maintenance of electric generators. The Knowledge Base is made to list the most common faults first; then the hypotheses areassociated with a certain probability. The processing of collected information is carried out according to Bayes’ method, which is based on the classical probability theory. In order to decide upon a failurehappening within the context of certain facts, a calculation of true values is carried out, which will help in developing an ideal diagnostic program during further research.